A Study on Institutional, Market and Natural Environment Impact on Agrarian Sustainability in Bulgaria - BACHEV, Hrabrin; TERZIEV, Dimitar (Journal of Environmental Management and Tourism, 2018)
The specific system of governance is a critical factor, which to a great extent (pre)determines the type and speed of development in different countries, industries, regions, communities, etc. This article tries to fill the gap and assesses the impact of institutional environment on agrarian sustainability in Bulgaria. The interdisciplinary New Institutional Economics framework is applied and assessment made on specific effects of major components of the “external” institutional environment on agrarian sustainability level in different administrative, geographical and ecological regions, subsectors of agriculture, and farms of various juridical type and size. Our study has found out that individual elements of external institutional, market and natural environment affect quite unequally farms of different types, individual subsectors of agriculture, and specific ecological and geographical regions. This type of studies is to be expended and their precision and representation increased. The latter however, requires a close cooperation between all interested parties, and participation of the farmers, agrarian organizations, local and central authorities, interest groups, research institutes and experts, etc.